Processes and ore deposits of ultramafic-mafic magmas through space and time - Mondal, Sisir K.; Griffin, William L. (Oxford Elsevier, 2018)
Processes and Ore Deposits of Ultramafic-Mafic Magmas through Space and Time focuses on the fundamental processes that control the formation of ore deposits from ultramafic-mafic magmas, covering chromite, platinum-group element (PGE), Ni-sulfides and Ti-V-bearing magnetite. The exploration, exploitation and use of these magmatic ores are important aspects of geology and directly linked to the global economy. Magmatic ores form from ultramafic-mafic magmas and crystallize at high-temperature after emplacement into crustal magma chambers, and are genetically linked to the evolution of the parental magmas through space and time. This book features recent developments in the field of magmatic ore deposits, and is an essential resource for both industry professionals and those in academia.--Provided by publisher.
Global- to deposit-scale controls on orthomagmatic Ni-Cu(-PGE) and PGE reef ore formation -- Review of predictive and detective exploration tools for magmatic Ni-Cu-(PGE) deposits, with a focus on komatiite-related systems in western Australia -- Metallic ore deposits associated with mafic to ultramafic igneous rocks -- Mixing and unmixing in the Bushveld complex magma chamber -- Secular change of chromite concentration processes from the Archean to the Phanerozoic -- Petrogenetic evolution of chromite deposits in the Archean greenstone belts of India -- New insights in the origin of ultramafic-mafic intrusions and associate Ni-Cu-PGE sulfide deposits of the Noril'sk and Taimyr provinces, Russia: evidence from radiogenic- and stable-isotope data -- Magmatic sulfide and Fe-Ti oxide deposits associated with mafic-ultramafic intrusions in China -- Alaskan-type complexes and their associations with economic mineral deposits -- Experimental aspects of platinum-group minerals
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Magmatism; Ore deposits; Geochemistry; Electronic books